2008
DOI: 10.1080/09523980802283608
|View full text |Cite
|
Sign up to set email alerts
|

Power Users and patchworking – An analytical approach to critical studies of young people’s learning with digital media

Abstract: This paper sets out to problematize generational categories such as 'Power Users' or 'New Millennium Learners' by discussing these in the light of recent research on youth and ICT. We then suggest analytic and conceptual pathways to engage in more critical and empirically founded studies of young people's learning in technology and media-rich settings. Based on a study of a group of young 'Power Users' it is argued, that conceptualising and analysing learning as a process of patchworking can enhance our knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
0
6
0
2
Order By: Relevance
“…Studies with a media background have some specific interests, like visual literacy as one form of new content, but it was connected to traditional media education (Lin and Polaniecki 2008). Ryberg and Dirckinck-Holmfeld (2008) focused on conceptualising and analysing learning as a process of patchworking and they investigated the ways in which "Power Users" use digital media. Researchers concluded that the skills of highly ICT-literate young people in a learning context was not restricted only to media literacies but they also exhibited reflective and critical abilities, and they had complex competences in terms of work processes integrating the "form" to the "content or substance".…”
Section: Media Studies As a Background Domainmentioning
confidence: 99%
“…Studies with a media background have some specific interests, like visual literacy as one form of new content, but it was connected to traditional media education (Lin and Polaniecki 2008). Ryberg and Dirckinck-Holmfeld (2008) focused on conceptualising and analysing learning as a process of patchworking and they investigated the ways in which "Power Users" use digital media. Researchers concluded that the skills of highly ICT-literate young people in a learning context was not restricted only to media literacies but they also exhibited reflective and critical abilities, and they had complex competences in terms of work processes integrating the "form" to the "content or substance".…”
Section: Media Studies As a Background Domainmentioning
confidence: 99%
“…Subsequently, we labelled the user clusters according to the main activity group in each cluster: Traditionalists are mainly engaged in the traditional interactive media activities grouped under ‘interacting’; Gamers engage in performing; Networkers in social software grouped under ‘interchanging’; and finally, Producers create content, in a ‘patchworking’ manner (cf. Ryberg & Dirckinck‐Holmfeld 2008), by means of for instance weblog‐templates or pre‐defined photo albums. These often standardized objects enable activities grouped under ‘authoring’.…”
Section: Resultsmentioning
confidence: 99%
“…Eynon 2010). A number of surveys among university students with a focus on ICT skills in relation to learning (Cameron 2005; Margaryan & Littlejohn 2008; Ryberg & Dirckinck‐Holmfeld 2008; Jones et al . 2009; Kerawalla et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Le remix ressemble à ce que (Ryberg et Dirckinck-Holmfeld, 2008) nomment « patchworking » ou l'approche de courtepointe, qui est une utilisation de divers bouts de textes pour une nouvelle création. C'est beaucoup plus qu'un copier-coller, car il s'agit de l'agencement d'informations afin de créer une vision originale, une argumentation inédite qui ainsi nécessite, d'après Ryberg (2008), une réflexion critique.…”
Section: Littératies Remix Et Créacollage Numériqueunclassified